2019
DOI: 10.24191/myse.v1i1.5559
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Green Perception and Behavior

Abstract: This study examined how student at UiTM Bandaraya Melaka perceived green practices. Convenient sample of 200 respondents were surveyed.  Students have positive perception towards green and findings show there is no significant difference on perception and there is significant difference in doing green activity.  Result indicated that “recycle paper” is the most chosen activity done by respondents whereas “attending green conference” is the least activity respondent chose to get involve. The implications of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…There is a debate over concern that in general students' have a positive and encouraging attitude towards green technology but their willingness to participate accordingly raises a lot of unwanted questions and uncertainties over the findings (Salas-Zapata et al, 2018). This finding is coherent with a number of studies that found out their respondents' attitude is higher and better than the level of knowledge (Mustapha et al, 2019;Md Kassim & Puteh, 2018;Bashirun, Badrolhisam, & Johari, 2016;Erhabor & Don, 2016). The positive attitude among the students denotes that green technology has great prospect in actualizing its goals as a great solution to all environmental issues in the country (Erhabor & Don, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…There is a debate over concern that in general students' have a positive and encouraging attitude towards green technology but their willingness to participate accordingly raises a lot of unwanted questions and uncertainties over the findings (Salas-Zapata et al, 2018). This finding is coherent with a number of studies that found out their respondents' attitude is higher and better than the level of knowledge (Mustapha et al, 2019;Md Kassim & Puteh, 2018;Bashirun, Badrolhisam, & Johari, 2016;Erhabor & Don, 2016). The positive attitude among the students denotes that green technology has great prospect in actualizing its goals as a great solution to all environmental issues in the country (Erhabor & Don, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Besides, many voluntary green behaviors undertaken by employees have gone unnoticed by the management system (Bashirun et al, 2019). Therefore, it is crucial to look inti the factors that influence employees' green behaviors in the workplace while considering organizational citizenship behavior towards environment, as most of environmental management studies have failed to distinguish between employees' voluntary and policy-driven involvement in green behaviors.…”
Section: Problem Statementmentioning
confidence: 99%